PENGARUH PENDIDIKAN, PELATIHAN DAN KOMPENSASI FINANSIAL TERHADAP KINERJA PEGAWAI - Wa Ode Linda Irawaty; Nurwati Nurwati; La Hatani Hatani (Pascasarjana Universitas Halu Oleo, 2017)
The purpose of this study was to examine and explain the effect of education, training, and financial compensation, either partially or simultaneously, on performance of extension workers at the Office of Forestry of Muna regency. The study used a survey design and explanatory research approach. Data were collected through cross section using a questionnaire. Respondents of the study were 33 agricultural extension workers at the Office of Forestry of Muna regency. To test hypotheses, the Multivariate Regression Analysis (MRA) was used. Results of the study showed that of education, training, and financial compensation, either partially or simultaneously, had positive and significant effects on performance of extension workers at the Office of Forestry of Muna regency. It could therefore be concluded that increasing education, training, and financial compensation as reflected or prioritized in the match of highest educational background and their job as extension workers, trainer’s/instructor’s ability to present training materials according to their qualification and to motivate trainees, and financial compensation, can positively and significantly contribute either partially or simultaneously to the improvement of the extension workers’ performances.Keywords: education, training, financial compensation, performance of agricultural extension workers